Engineered substrate for electronic and photonics application - Eow, Desmond Fu Shen (2018)
Silicon (Si) has been the most prominent material for electronic where complementary metal-oxide-semiconductor (CMOS) integrated circuitry has been fabricated using Si since its invention. In recent years, the integration of III-V photonics application on Si platform which is expected to provide promising features such as Micro-LED, high mobility transistor and on-chip optical communication has been wide studied. This integration between III-V compound such as GalliumArsenide (GaAs) and Si substrate is facing the issues of lattice mismatch. GaAs substrate has a lattice constant of 5.653 Å, while Si has a lattice constant of 5.431 Å. This 4.1% of lattice mismatch results a large threading dislocation densities (>108cm-2) which in turns causes the poor performance of the integration.The prime aim of this final year research project is to evaluate the quality of AlGaInP multi-quantum wells (MQWs) red LED (peak wavelength ~ 668 nm) structure epitaxial growth on silicon substrate through different buffer layers, such as germanium on silicon (Ge/Si), germanium on silicon dioxide (GOI) and arsenic-doped germanium on silicon (Asdoped Ge/Si). LEDs on commercially obtained Ge/Si, GaAs, and Germanium (Ge) are also studied for comparison purpose. Therefore, electrical and optical measurements will be performed on different samples to quantify and analyse the performance of the LED structure on different substrates. The end goal is to integrate AlGaInP LED structure on silicon substrate in order to enhance its performance and functionality.